Improving the Efficiency of Dynamic Virtual Machines Consolidation in Cloud Data Centers - دندة, رضوان; قبلان, قاسم; رجب, حيان (Latakia University Journal -Engineering Sciences Series, 2021)
Inefficient resource usage is one of the greatest causes of high energy consumption in cloud data centers. To solve the problem, researchers presented Dynamic consolidation of virtual machines technique, which aim to consolidate VMs in minimum number of hosts (physical machines). However, aggressive consolidation of VMs leads to an increase in the number of migrated VMs, and hosts suffering from Overloading. This in turn affects the quality of service (QoS) of the applications running in the VMs. So, it is important to balance between guaranteeing Quality of Service (QoS) and saving energy. In this research, we introduce Proactive Adaptive Dynamic Consolidation Algorithm to reduce energy consumption while maintaining the required performance levels in a cloud data center. We have performed experimental evaluation on Cloudsim toolkit to validate the effectiveness of the proposed algorithm with real-world workloads, and compare its performance against a collection of many previous works in this field which includes the following algorithms: LR/MMT/SM/MBFD, LR/MMT/PA/RUA, LR/MMT/SM/Shi-AC, LR/MMT/SM/MFPED, EES. The simulation results showed that the suggested algorithm outperforms these algorithms regarding energy consumption, QoS guarantees, and the number of VM migrations